2015
DOI: 10.18632/oncotarget.5190
|View full text |Cite
|
Sign up to set email alerts
|

Rapid targeted somatic mutation analysis of solid tumors in routine clinical diagnostics

Abstract: Tumor genotyping is an essential step in routine clinical practice and pathology laboratories face a major challenge in being able to provide rapid, sensitive and updated molecular tests.We developed a novel mass spectrometry multiplexed genotyping platform named PentaPanel to concurrently assess single nucleotide polymorphisms in 56 hotspots of the 5 most clinically relevant cancer genes, KRAS, NRAS, BRAF, EGFR and PIK3CA for a total of 221 detectable mutations. To both evaluate and validate the PentaPanel pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…We observed a relationship between the frequency of a mutated allele in the sample and the amount of DNA required for detection. This is partially in contrast to the findings of Magliacane et al (2015), who reported that mutations could be detected even using very small amounts of DNA (1 ng per reaction) [28]. In particular, we observed that, in the presence of highly represented mutations (about 20%), only a very small amount of DNA (about 5 ng) was sufficient for the detection.…”
Section: Discussioncontrasting
confidence: 99%
“…We observed a relationship between the frequency of a mutated allele in the sample and the amount of DNA required for detection. This is partially in contrast to the findings of Magliacane et al (2015), who reported that mutations could be detected even using very small amounts of DNA (1 ng per reaction) [28]. In particular, we observed that, in the presence of highly represented mutations (about 20%), only a very small amount of DNA (about 5 ng) was sufficient for the detection.…”
Section: Discussioncontrasting
confidence: 99%
“…(33) New mutational analyses have led to understanding cancer mutations that occur across organ systems to allow for the design of specific basket trials, where therapies can be rationally targeted towards specific mutations. (34) Alternative splicing is another mechanism by which alternative isoforms may have significant impact on gene expression and function, independent of genetic mutations. (8) In this study, a novel algorithm is utilized to systematically identify alternative splicing events unique to tumors to show that alternative splicing can represent an important functional mechanism of oncogenesis in HPV-related oropharyngeal cancer that has not been previously appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assume that it might be a LINC00312-dependent network which provided subtle yet decisive regulation of cell proliferation and transformation in keloids, which might also be found in other highly recurrent benign tumours. The third most up-expressed lncRNA was HOXA11-AS, which was also documented to increase the progression of glioma [27, 28] and human uterine cervix carcinoma [29, 30]. Also, the functional variant of HOXA11-AS has been revealed to inhibit the oncogenic phenotype of epithelial ovarian cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…The third most up-expressed lncRNA was HOXA11-AS, which was also documented to increase the progression of glioma [27, 28] and human uterine cervix carcinoma [29, 30]. Also, the functional variant of HOXA11-AS has been revealed to inhibit the oncogenic phenotype of epithelial ovarian cancer [30]. To the best of our knowledge, keloid is the only benign tumour in which HOXA11-AS has been documented aberrantly changed.…”
Section: Discussionmentioning
confidence: 99%